Toxicity and Safety Analysis of Polyhexamethylene Guanidine: A Comprehensive Systematic Review - Ivanov, Ivan; Kirillova, Daria; Erimbetov, Kenes; Shatalov, Denis (Sciences of Pharmacy, 2024)
Polyhexamethylene guanidine (PHMG) is a commonly used disinfectant, but safety concerns have arisen due to poisoning cases. This systematic review assesses the toxicity and safety of PHMG by inhalation, oral administration, skin contact, and ocular contact to determine its potential medical applications and acceptable concentration limits. Searches in PubMed, ScienceDirect, CENTRAL, and CyberLeninka up to January 2024 identified 11 in vitro studies with human cell lines, 28 animal studies, and 10 articles involving patients and healthy volunteers. The review found that inhalation of PHMG leads to pulmonary fibrosis and malignant neoplasms, making aerosol forms unacceptable. PHMG can also affect liver function and have adverse effects on the heart, kidneys, and hematopoietic system. For dermal use, PHMG appears to be safe at concentrations up to 3%, although practical use may limit this to 1% due to potential discomfort. Still, it is important to consider possible sensitization, especially in patients with pre-existing skin conditions. In oral hygiene, 1% PHMG-P has been used safely in periodontal treatment, suggesting its potential in dentistry. For ophthalmic use, concentrations should be carefully monitored. PHMG-P solutions below 0.13% appear to be safe for human corneal epithelium, however lower concentrations still pose a risk of corneal fibrosis, as shown in animal studies. Physicians should prefer lower concentrations and consider alternatives or formulations with reduced toxicity for sensitive applications such as eye drops. Overall, although PHMG and its derivatives show promise in a variety of medical applications, their use should be reasonable, with careful consideration of the associated risks.